2020 International Symposium on Networks, Computers and Communications (ISNCC) 2020
DOI: 10.1109/isncc49221.2020.9297264
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Adversarial DDoS attack on IDS using GAN

Abstract: IDS are essential components in preventing malicious traffic from penetrating networks. IDS have been rapidly enhancing their detection ability using ML algorithms. As a result, attackers look for new methods to evade the IDS. Polymorphic attacks are favorites among the attackers as they can bypass the IDS. GAN is a method proven in generating various forms of data. It is becoming popular among security researchers as it can produce indistinguishable data from the original data. I proposed a model to generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 24 publications
(31 reference statements)
0
16
0
Order By: Relevance
“…Chauhan et al [33] used GANs to demonstrate that deep learning methods were not sufficient in the detection of new attack profiles. They first trained a GAN based on the CICIDS2017 [32] dataset and used the SHapley Additive exPlanations (SHAP) [34] method to extract features from the dataset based on their importance and impact on the output.…”
Section: Related Workmentioning
confidence: 99%
“…Chauhan et al [33] used GANs to demonstrate that deep learning methods were not sufficient in the detection of new attack profiles. They first trained a GAN based on the CICIDS2017 [32] dataset and used the SHapley Additive exPlanations (SHAP) [34] method to extract features from the dataset based on their importance and impact on the output.…”
Section: Related Workmentioning
confidence: 99%
“…An area under curve (AUC) score of 75% is also reported, proving that the evaluator cannot differentiate between the real data and the generated synthetic data. In [36], it is shown that even after defensive systems are developed which employ incremental learning, they can still be vulnerable to new attacks if the attack profile is changed. Another challenge while detecting DoS and DDoS attacks is to be able to differentiate between the flash crowds and the actual attacks.…”
Section: Detecting Ddos Attacks Using Adversarial Machinementioning
confidence: 99%
“…Although [29,34,36,37] have described and proved that an AI model can be trained to generate new synthetic instances and fool the security systems, they have not provided any concrete solution on how a classifier can be trained to detect such kind of generated synthetic adversarial instances. An attacker can use these generated synthetic instances to generate evasion attacks on the security systems to make the classifier misclassify those samples.…”
Section: Detecting Ddos Attacks Using Adversarial Machinementioning
confidence: 99%
See 1 more Smart Citation
“…Chauhan and Heydari [32] implemented polymorphic DDoS attacks using GANs in order to assess NIDS's ability at detecting adversarial examples and to enhance the training process for better resilience. The polymorphic DDoS attacks are generated by updating the DDoS attack profile features (i.e., number of features and swapping features), merging them with the previously created adversarial examples, and feeding them to the GAN model.…”
Section: A Generation Of Aes To Attack Ml-based Nids Modelsmentioning
confidence: 99%